(untitled) (CIPEEX, 2025)
An aneurysm is a chronic and complex inflammatory process of the arterial wall that causes permanent dilation of the vessel wall in a localized area, with several complications. It can result from degenerative, inflammatory, or infectious processes, genetic alterations, or even trauma. Some studies report a relationship between the development of inflammatory aortic aneurysms (IAA) and immunoglobulin G4-related disease (IgG4-RD). Based on this parallel, the present study aims to identify the target of this immunoglobulin within AAA pathology, as well as how to reverse the action of IgG4 in these blood vessels, whether medically or surgically. Thus, this project is justified by the perspective of elucidating the forms of treatment for abdominal aortic aneurysms, in order to contribute to the conduct of vascular surgeons when faced with cases involving AAA. To this end, this study consists of an integrative review that aims to document the findings that contribute to the relationship between IgG4 and abdominal aortic aneurysm, in order to provide knowledge on how to approach and treat it appropriately.